The association of PD-L1 expression status and the PD-1/PD-L1 inhibitor-related toxicity profile in non-small cell lung cancer - Qian Zhu; Hao Hu; Li-Ying OuYang; Rong Yang; Wen-Xiao Wei; Pin Huang; Xin-Rong He (BMC Cancer)
Abstract Objective While PD-L1 expression serves as a predictive biomarker for programmed cell death 1 and its ligand (PD-1/PD-L1) inhibitor efficacy in patients with non-small cell lung cancer (NSCLC), its association with treatment-related adverse events (TRAEs) has yet to be fully elucidated. This study systematically evaluated the correlation between PD-L1 expression status and TRAEs in patients with NSCLC. Methods We systematically searched the Cochrane Library, Embase, and PubMed databases from inception to June 30, 2024, to identify prospective clinical trials examining PD-1/PD-L1 inhibitors among NSCLC patients that reported treatment-related toxicity data stratified by PD-L1 expression. Results Twenty-six prospective trials (N = 5,453) were analyzed. At the 1%, 25%, and 50% PD-L1 cutoffs, PD-L1-negative patients presented significantly reduced risks of grade 3–4 TRAEs (OR = 0.37, 0.53, 0.41; 95% CI = 0.18–0.77, 0.31–0.90, 0.19–0.97; P < 0.01, 0.02, 0.04). Similarly, PD-L1-negative patients had significantly reduced risks of AEs leading to treatment discontinuation at the 1% and 25% PD-L1 cutoffs (OR = 0.25, 0.38; 95% CI = 0.08–0.76, 0.16–0.89; P = 0.01, 0.03) but not at the 50% PD-L1 cutoff (OR 0.28, 95% CI 0.07–1.12, P = 0.07). Subgroup analyses revealed elevated all-grade TRAEs with the 22C3 immunohistochemistry assay (P < 0.001), whereas first-line therapy recipients (P = 0.006) and open-label trial participants (P = 0.002) presented increased grade 3–4 TRAEs. Conclusions PD-L1 positivity may predict increased risks of grade 3–4 TRAEs and AEs leading to treatment discontinuation in NSCLC patients receiving PD-1/PD-L1 blockade. Furthermore, PD-L1 expression might be a useful biomarker for toxicity management in patients with NSCLC after PD-1/PD-L1 inhibitor treatment.